ChemInform Abstract: Organocatalyzed Intramolecular Michael Addition of Morita—Baylis—Hillman Adducts of β‐Arylnitroethylenes: An Entry to 3‐Aryl‐4‐nitrocyclohexanones. Issue 14 (20th March 2013) - Reddy, Chada Raji; Reddy, Motatipally Damoder; Haribabu, Kothapalli
Abstract Reactions with L‐proline proceed with less than 20% enantiomeric excess.